A history of Western educational ideas - Lawton, Denis; Gordon, Peter 1927- (Woburn Press, 2002)
This work traces the development of Western educational ideas from the Greek society of Socrates, Plato and Aristotle, to the ideas and ideologies behind some of the controversial issues in education today. The authors avoid the traditional "great thinkers" approach, and instead try to relate educational ideas to the political, social and economic development of the times, covering Greece and Rome, early Christianity, the Renaissance, the religious conflicts of the 15th and 16th centuries, the Enlightenment in the 18th century, and Romanticism, as well as more familiar political issues in the 19th and 20th centuries. The book concludes with a brief discussion of the problem of values and education in the 21st century. The authors reject extreme versions of postmodernist thinking, and reassert the view that values and an expression of priorities within value systems are an essential aspect of educational planning at any time.
Keywords: Ideeëngeschiedenis; Pedagogiek; Westerse wereld; Éducation - Philosophie - Histoire; Erziehung; Geschichte; Philosophie; Pädagogik; Education -- Philosophy -- History; Erziehungsphilosophie; Bildungstheorie